2006
DOI: 10.1111/j.1399-6576.2006.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guidance improves the success rate of a perivascular axillary plexus block

Abstract: Ultrasonographic guidance improves the overall success rate of axillary blocks in comparison to a transarterial technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
2
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(90 citation statements)
references
References 18 publications
8
70
2
10
Order By: Relevance
“…Sixth, we believed LA would be better distributed in the SA group within the sheath of axillary brachial plexus, but we did not confirm intra-sheath placement of the needle tip or LA distribution by ultrasound or contrast radiography [1]. Furthermore, we did not consider septae dividing the brachial plexus within the sheath.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sixth, we believed LA would be better distributed in the SA group within the sheath of axillary brachial plexus, but we did not confirm intra-sheath placement of the needle tip or LA distribution by ultrasound or contrast radiography [1]. Furthermore, we did not consider septae dividing the brachial plexus within the sheath.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we believe MCN block did not affect our assessment of the effectiveness of TAAB, because MCN sensory block scores were similar in the two study groups (Table 3). In addition, we did not include surgeries of the anterior-lateral forearm, had we done so complete blockade of the MCN would have confounded results regardless of the success of TAAB [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may explain the lack of difference in success rates between US and neurostimulation (NS). Using a technique relying on multiple injections to achieve circumferential LA spread around the artery, Sites et al 15 compared US guidance to a transarterial technique (with two equal volume injections in front and behind the artery) in 56 patients undergoing hand surgery. Using 35 mL of lidocaine 1.5% with epinephrine 5 µg·mL -1 , these authors found that echoguidance yielded a shorter performance time (7.9 ± 3.9 vs 11.1 ± 5.7 min; P < 0.05) and a lower failure rate, defined as conversion to general anesthesia or the inability to localize the artery (0 vs 28.6% of patients; P = 0.01).…”
Section: Adjunctive Ultrasonography Axillary Block (Axb)mentioning
confidence: 99%